2006
DOI: 10.1007/s00221-006-0423-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of speed manipulation on the control of aperture closure during reach-to-grasp movements

Abstract: This study investigates coordination between hand transport and grasp movement components by examining a hypothesis that the hand location, relative to the object, in which aperture closure is initiated remains relatively constant under a wide range of transport speed. Subjects made reach-tograsp movements to a dowel under four speed conditions: slow, comfortable, fast but comfortable, and maximum (i.e., as fast as possible). The distance traveled by the wrist after aperture reached its maximum (aperture closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
6
26
1
Order By: Relevance
“…In line with previous studies, which had shown that closing time (Laurent et al, 1994;Rand & Stelmach, 2005;Rand et al, 2006Rand et al, , 2008Zaal & Bootsma, 2004) and closing distance (e.g., Carnahan & McFadyen, 1996;Rand & Stelmach, 2005;Rand et al, 2006;Wang & Stelmach, 2001;Watson & Jakobson, 1997;Zaal & Bootsma, 2004;Zaal et al, 1998) varied with factors such as object velocity, object orientation, object width, object size, reaching amplitude, and reaching velocity, we found a large effect of the velocity with which the object approached on these two variables. The effects of object velocity on these two factors that came out of our experiment corroborated the conclusion that closing time or distance are not being kept constant, and, thus, do not act as control variables in the coordination of reaching and grasping or in the timing of catching in the situation that the hand is not moving.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with previous studies, which had shown that closing time (Laurent et al, 1994;Rand & Stelmach, 2005;Rand et al, 2006Rand et al, , 2008Zaal & Bootsma, 2004) and closing distance (e.g., Carnahan & McFadyen, 1996;Rand & Stelmach, 2005;Rand et al, 2006;Wang & Stelmach, 2001;Watson & Jakobson, 1997;Zaal & Bootsma, 2004;Zaal et al, 1998) varied with factors such as object velocity, object orientation, object width, object size, reaching amplitude, and reaching velocity, we found a large effect of the velocity with which the object approached on these two variables. The effects of object velocity on these two factors that came out of our experiment corroborated the conclusion that closing time or distance are not being kept constant, and, thus, do not act as control variables in the coordination of reaching and grasping or in the timing of catching in the situation that the hand is not moving.…”
Section: Discussionsupporting
confidence: 93%
“…In Figs. 1C and D,hand aperture is plotted as a function of actual distance to contact (i.e., hand-object distance), a less familiar representation, although given in a subset of prehension studies that stress the role of distance rather than time (e.g., see Haggard & Wing, 1998;Rand, Squire, & Stelmach, 2006;Wallace, Stevenson, Spear, & Weeks, 1994;Wing & Fraser, 1983;Zaal & Bootsma, 2000). Finally, Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most often, when the coordination of prehension has been addressed, hypotheses regarding the moment of peak hand aperture, the moment that hand opening goes into hand closing, have been put forward (for an overview, see Zaal and Bootsma 2004). For instance, it has been proposed that peak hand aperture would occur at the moment of peak deceleration of the reaching movement (Jeannerod 1984), at a Wxed time (Gentilucci et al 1992) or distance (Rand and Stelmach 2005;Rand et al 2006;Stelmach 1998, 2001) before hand-object contact, or that coordination is based on time-to-contact information (Bootsma and Van Wieringen 1992;Zaal and Bootsma 2004;Zaal et al 1998). In our opinion, the latter hypothesis is the most promising of the ones currently available, but it certainly still needs a critical test.…”
Section: Introductionmentioning
confidence: 99%